2022
DOI: 10.1088/1755-1315/1121/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics uptake in wild Asian green mussels sampled from Pasir Putih estuary in Johor, Malaysia

Abstract: The high concentrations of plastic and plastic debris in the environment continue to rise each year as most plastics undergo minimal biological degradation. As plastics are exposed to sunlight, the atmosphere, and water, these polymers break into smaller pieces and become individual polymer molecules. In this study, the presence of microplastics (MPs) in mussels was investigated. Wild Asian green mussels (Perna viridis) samples were collected from the Pasir Putih estuary for 3 months and were categorised accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…This indicates a potential increase in heavy metal effluent discharge from industrial areas over the decade. The study from Zahid et al [26] on the microplastic accumulation in green mussels at the same site found that the smaller green mussels accumulated more microplastic inside the soft tissue than the larger-sized mussel, suggesting that microplastic accumulation might also be the potential factor that affected shell deformities. Other possible factors, such as polonium (Po) contamination, were higher in wild green mussels than the cultured and market green mussels due to direct contamination from industrial and domestic discharges [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates a potential increase in heavy metal effluent discharge from industrial areas over the decade. The study from Zahid et al [26] on the microplastic accumulation in green mussels at the same site found that the smaller green mussels accumulated more microplastic inside the soft tissue than the larger-sized mussel, suggesting that microplastic accumulation might also be the potential factor that affected shell deformities. Other possible factors, such as polonium (Po) contamination, were higher in wild green mussels than the cultured and market green mussels due to direct contamination from industrial and domestic discharges [28].…”
Section: Discussionmentioning
confidence: 99%
“…Shell deformities in green mussels were suggested to be influenced by many factors, such as the presence of heavy metal contamination (Cd and Cu) that were discharged by the nearby industrial areas, hydrocarbons contamination [25], as well as microplastic contamination from [26]. Yap et al [27] previously found that 9.52% of the green mussels in Kg.…”
Section: Discussionmentioning
confidence: 99%